Telomere loss in cells treated with cisplatin - Ishibashi, Toru (The National Academy of Sciences, 1998)
Telomeres play an important role in the immortalization of proliferating cells. The long tandem repeats of 5′-TTAGGG-3′ sequences in human telomeres are potential targets for the anticancer drug cisplatin, which forms mainly intrastrand d(GpG) and d(ApG) cross-links on DNA. The present study reveals that telomeres in cisplatin-treated HeLa cells are markedly shortened and degraded. A dose that killed 61% of the cells but allowed one round of cell division resulted in shortened telomeres before the induction of apoptosis. Higher doses of cisplatin halted cell cycle progression during the first S phase and triggered apoptosis followed by degradation of telomere repeats. A model in which both cell division with incomplete replication and induction of apoptosis by cisplatin could occur was devised to explain the drug-induced telomere loss.